USING NETWORK PLATFORMS TO DETERMINE THE QUALITY OF SERVICE: A CASE STUDY OF TASHKENT HOTELS - Nigina Rakhmonova (Ecominds Press, 2025)
The role of IT in the hotel service is incomparable, while web sites serve as a mirror in managing the hotel business, working with customers, and determining the quality of service. In addition, network platforms are becoming increasingly important for hotel companies to enter and present themselves in the tourism market. As a clear example of this in our research, we used booking.com an online platform which is designed specifically for the hotel industry, to determine the quality of hotel service and to exchange opinions with thousands of customers. In this article, the extent to which the potential of hotel service personnel affects the quality of service and the guest satisfaction is studied on the example of 49 small hotels located in Tashkent. Using the 360-degree feedback method, the potential of the enterprise manager was determined, and the quality of service was evaluated on the platform of booking.com based on the opinions of more than 1000 foreign and local tourists about the service provided in these 49 hotels. The questionnaire consists of 2 parts, in the first part, the ability of employees was checked according to 16 indicators, and in the second part, of course, the factors affecting their existing potential were analyzed, and it was determined that the factor such as education, staff competence and gender is statistically significant.
Keywords: Network platforms, service quality, hotel staff competence, indicators determining ability, factors affecting to potential.